DEFINITION OF THE CONCEPT OF «WASTE» AS A LEGAL CATEGORY - Kononuchenko, Ivan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to define the concept of «waste» as a legal category. Research methods: the solution to the set goal was carried out using special scientific and general scientific methods of cognition, among which structural-logical, synthesis and analysis, dialectical, comparative-legal methods are distinguished. Results: the characterization of waste as objects of legal relations should include a set of such signs as: 1) impossibility of obtaining useful properties of things, substances, materials by the owner or owner; 2) lack of intention of the owner or possessor of such an object to continue actual possession, which must be demonstrated openly. Discussion: it is determined that one person’s rejection of objects that have lost their useful properties does not mean that other persons do not intend to own, use or dispose of them, which is evidenced by the provisions of Art. 332 of the Civil Code of Ukraine, which establishes the acquisition of ownership of a processed item, including an item made from waste. The author concludes that the characterization of waste as objects of legal relations should include a set of such signs as: 1) the impossibility of obtaining useful properties of things, substances, materials by the owner or possessor; 2) lack of intention of the owner or possessor of such an object to continue actual possession, which must be demonstrated openly. At the same time, the refusal of one person from objects that have lost their useful properties for him does not mean that other persons do not intend to own, use or dispose of them, which is evidenced by the provisions of Art. 332 of the Civil Code of Ukraine, which establishes the acquisition of ownership of a processed item, including an item made from waste. These conclusions require changes to the current legislation of Ukraine, which will be the subject of further copyright searches.